PERAN PROBABILITAS DALAM PENGAMBILAN KEPUTUSAN PADA KOMUNIKASI INTERPERSONAL SEHARI-HARI: STUDI KEPUSTAKAAN - Azna, Nida Farizatul; Ismatillah, Laila; Adawiah, Hanifah Salma; Rahman, Julia; Nisa, Iskarimatun; Ruwardi, Alvira Mihada; Kurniyawan, Ardi; Sulistyani, Anjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of probability in decision-making within everyday interpersonal communication through a literature review approach. Communication is understood as a decision-making process under conditions of uncertainty, including determining the message content, the appropriate timing, and the most effective way to deliver it. Among the three types of probability, subjective probability is considered the most relevant because it is based on individual experience, intuition, and perception. The findings indicate that people unconsciously apply probabilistic reasoning before communicating, such as estimating the listener’s response, the likelihood of a request being accepted, or the most suitable communication medium. This concept is reflected in choosing the right time to deliver bad news, resolving conflicts, and deciding whether to use chat or phone calls. The study concludes that probability enhances communication effectiveness, reduces conflicts, strengthens interpersonal relationships, and helps individuals manage uncertainty. For students of Islamic Communication and Broadcasting, this understanding provides valuable knowledge for developing more effective, adaptive, and thoughtful communication skills.